Legal and Operational Aspects of Compliance with Scientific Integrity - Monique Weber-Mandrin; Michael Daphinoff; Ines C. Weber (CHIMIA)
Ensuring scientific integrity is of utmost importance in the research community, as it forms the foundation of reliable and credible scientific knowledge. Compliance with scientific integrity involves adhering to ethical principles, research standards, and legal regulations that promote transparency, honesty, and accountability. Fabrication, falsification, and plagiarism are common forms of research misconduct that undermine the credibility and trustworthiness of scientific findings. Institutions must establish clear policies and procedures to address and prevent such misconduct, including mechanisms for reporting, investigation, and appropriate disciplinary actions. This article examines the legal and operational aspects related to compliance with scientific integrity, highlighting key considerations and best practices in this critical domain.